33. SYSTEMATIC REVIEW AND META-ANALYSIS OF BREAST CANCER BRAIN METASTASIS AND PRIMARY TUMOR RECEPTOR EXPRESSION DISCORDANCE. (4th August 2020) - Kotecha, Rupesh; Tonse, Raees; Rubens, Muni; McDermott, Michael; Odia, Yazmin; Appel, Haley; Mehta, Minesh
Abstract: BACKGROUND: Discordance in hormone receptor (estrogen [ER] and progesterone [PR]) and human epidermal growth factor receptor2 (HER2) status between the primary tumor and brain metastases and its effect on tumor classification subtype switching has been described but remains understudied. METHODS: Using the PRISMA guidelines, a systematic review was performed of series published prior to April 2020 of biopsied or resected breast cancer brain metastasis (BCBM) from the Medline database using the keywords "breast cancer" and "brain metastasis" combined with "estrogen receptor/ER, " "progesterone receptor/PR, " "HER2/neu, " and "receptor conversion/dis- or concordance." Weighted random effects models were used to calculate pooled estimates. RESULTS: Fifteen full-text articles met inclusion criteria and cumulatively reported on 1373 patients who underwent biopsy or resection of at least one BCBM to compare to their primary tumor. At initial diagnosis, receptor expression profiles were 45.0% ER+, 41.0% ER-, 31.0% PR+, 51.0% PR-, 35% HER2+, and 47.0% HER2-. Corresponding receptor expression profiles from the BCBM were 19.0% ER+, 31.0% ER-, 13.0% PR+, 40.0% PR-, 21.0% HER2+, and 26.0% HER2-. Intra-patient receptor discordance comparisons revealed that 540 patients (42.6%) exhibited discordance in any receptor with 17.0% (95% CI: 13.0%-23.0%) discordance for ER status, 23.0% (95% CI: 18.0%-30.0%) for PR status, and 12.0% (95% CI: 8.0%-16.0%) for HER2 status. The most common receptor discordance events found in BCBM compared to primary tumors were ER loss 11.0% (95% CI: 8.0%-16.0%), PR loss 15.0% (95% CI: 11.0%-21.0%), and HER2 gain 9.0% (95% CI: 7.0%-11.0%). CONCLUSIONS: BCBM commonly exhibit receptor expression changes on comparison to primary tumors including a 10% HER2 gain rate, a potential actionable target. Classification patterns need to be updated to reflect changes in overall tumor subtype grouping and which factors predict for BCBM/primary tumor discordance. Overall, tumor subtype switching and its effect on clinical management remains underappreciated.